Comparative Study of Juvenile Delinquency and Non-Delinquencyâ€ - Vasan, Praveen; Poonam Rawat, Dr. (International Journal of Engineering and Technology, 2019)
Towards adulthood, one of the most complex developmental stages that young people experience is adolescence. During this stage, challenges are encountered relative to educational progress. These challenges are attributed to behavioral disorders, character deviations, and emotional disturbances. In this article, the main aim is to describe and analyze some of the differences that exist between non-delinquent and delinquent adolescents. Through a comparative analysis, the article focuses in non-delinquency and delinquency among juveniles. Indeed, the aspect of juvenile delinquency has continually received research interest among scholarly investigators aimed at gaining a deeper understanding of the delinquency phenomenon. The trend is not only motivated by the affirmation that adult delinquency tends to arise from juvenile delinquency but also due to the rich research information that many scholars have documented to accrue form in-depth analyses of the adolescents. It is also worth indicating that the research context is India and is deemed timely because of frequent changes that are being experienced in the countryâ€™s penitentiary and judicial systems. Indeed, the research is poised to give crucial insights into some of the mechanisms through which delinquency could be addressed among adolescents, eventually curbing possible adult delinquency with which juvenile delinquency is associated.Â